Identification and quantification of vitellogenin gene in eyebrow goby (Oxyurichthys ophthalmonema) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sa-An AC, Quinitio GF, Anasco NC, Traifalgar RFM, Nillos MGG. 2022. Identification and quantification of vitellogenin gene in eyebrow goby (Oxyurichthys ophthalmonema). Biodiversitas 23: 5606-5613. Vitellogenin (VTG) gene has been used as a biomarker for exposure to estrogenic compounds in marine and freshwater fish species. There was limited information about the detection of VTG mRNA in an estuarine environment using a bioindicator fish species. In this study, a quantitative real-time polymerase chain reaction (qPCR) assay was developed for quantification of VTG mRNA normalized to ?-actin in eyebrow goby, Oxyurichthys ophthalmonema. VTG mRNA in the liver of reproductively mature female samples was isolated, amplified, and sequenced. There were 430 bp fragments of VTG, corresponding to a 143 amino acid sequence obtained from eyebrow goby. The partial protein sequence exhibited similar identities with the phosvitin motif of VTG in other gobies. The new qPCR assay was developed through the evaluation of hepatic mRNA levels in nonreproductive male eyebrow goby at 0, 6, 12, and 24 h following intraperitoneal injection of 10 mg kg-1 17?-estradiol. Hepatic mRNA levels were detected 6 h after 17?-estradiol injection and the highest VTG expression was noted 24 h after injection. Results of the present study suggest that male eyebrow goby can be used as indicator species for estrogenic contamination. Likewise, the established qPCR assay can be used to assess recent exposure to estrogenic contaminants in the aquatic environment. The characterization of the amplified VTG gene from eyebrow goby and the application of the qPCR assay developed for eyebrow goby in monitoring EDCs in the field may be considered for future investigation.
Keywords: 17β-estradiol, endocrine disrupting chemical, mRNA indicator, Oxyurichthys ophthalmonema, qPCR , vitellogenin